Adoption of Cost-Saving Innovations by a Regulated Firm - Sweeney, George H. (American Economic Review, 1981)
Regulatory lag is generally credited with providing monetary incentives for the adoption of cost-saving technological changes by regulated firms. Because regulators can not instantaneously adjust price ceilings in response to cost changes, these incentives are inherent to the process of price regulation in a dynamic world. A firm which decreases production costs through technological innovation will enjoy excess profits until the regulators lower price to a level consistent with the new conditions.' The longer the delay before regulatory response to a decrease in cost, the greater are the profits which can be derived from a cost reduction, and, therefore, the greater is the incentive for adoption of technological change.2 The passive nature of this incentive mechanism is an important characteristic. Although regulatory agencies typically have authority to force price decreases upon firms which do not take advantage of potential cost savings, this power is limited by the difficulty of proving that a firm is laggard, rather than the victim of unfortunate circumstances. Thus, the regulated firm which foregoes potential profit from adopting a costsaving innovation today may generally reap that profit at some convenient time tomorrow. Indeed, it is the main contention of this paper that, in many circumstances, a regulated monopolist can maximize the present value of profits only by delaying adoption of an innovation. That is, rather than completely adopting a cost-saving innovation when it becomes available, a profit-maximizing regulated firm will choose to adopt the innovation only gradually through time. The profitability of such delaying procedure may be illustrated by a simple example. Consider a situation in which the price of a firm's product is fixed by a regulatory authority, but periodically adjusted according to the following cost-plus-markup scheme. At each review, price for the following period is set equal to average cost of the previous period plus an allowed markup. That is, price in period i + 1 is set equal to m times average cost in period i (m ) 1). This situation is illustrated in Figure 1. A firm is initially producing output QO at cost CO(QO), with price set by the regulators at mCO(QO)/QO. Suppose a cost-saving innovation is discovered, which, if employed, would decrease average production cost to C1(Q)/Q. If the firm were to adopt this innovation immediately, it would earn a profit equal to the area of the rectangle ABCD in Figure IA. At the next regulatory review, price would be lowered to the level m times the new average cost (i.e., to P1), and profit would fall to that amount represented by the area AEFG. This amount of profit would be earned each period thereafter. However, suppose that the firm were to adopt this innovation in two steps rather than completely adopting the innovation when it first becomes available. This option is sketched in Figure lB. In the initial period, the firm adopts the innovation throughout approximately half its operations, thereby lowering average cost only to OH. In the next period, the firm completes the adoption process, lowering average cost to the final level OA. Although this procedure would yield profit equal only to HICD in the initial period, it would result in a price in the next period equal to P1 (i.e., equal to m times OH). Since average cost in that period would fall to OA, profit would equal AJKL. In the next period, price would be at the new equilibrium level OG, and profit would equal AEFG. This amount of profit would be earned each period thereafter. Given the demand and cost functions illustrated in Figure 1, the second alternative *Assistant professor of economics, Vanderbilt University. 'See William Baumol, and Alfred Kahn, ch. 2. 2See Elizabeth Bailey.